Gator Bait - DeLeon, Jana (DeLeon, Jana. Miss Fortune series., 2014)
"Things are starting to look up for Fortune Redding. Even though her life was at stake, the CIA assassin had balked at taking on a new identity in Sinful, Louisiana. But instead of hating it like she'd thought she would, Fortune now has friends she cares about and just finished up an incredible first date with the sexiest deputy in the state. Sure, there's been a murder or two that she's gotten mixed up in since she arrived in town, but she's hoping all of that is behind her."--Back cover.